Estrategia para regularizar a los comerciantes informales de la Urbanización La Joya vial 8 del cantón Daule - Manosalvas Murillo, Luis Eduardo (2020)
This study aims to contribute with a plan to regularize the informal merchants located on the main avenue of the Urbanization La Joya to improve their current situation and boost entrepreneurship that benefits merchants and residents of the area. Informal commerce has been considered a sector of little importance due to its scarce contribution to the productive apparatus of the country, however, it should not be opposed to the control entities. The current economic situation of the country and the lack of formal employment have made people find in informal trade the opportunity to generate resources that allow them to contribute to the economy of their homes because in addition to finding unemployed people, we find people who have a job Stable per your income does not cove your monthly expenses…..